The Long Non-coding RNAs: Paramount Regulators of the NLRP3 Inflammasome - Menon, Mridula P.; Hua, Kuo-Feng (Frontiers in Immunology, 2020)
The NOD LRR pyrin domain containing protein 3 (NLRP3) inflammasome is a cytosolic multi-proteins conglomerate with intrinsic ATPase activity. The predominant presence in the immune cells emphasizes its significant role in the immune response. The downstream effector proteins IL-1β and IL-18 are responsible for the biological functions of the NLRP3 inflammasome upon encountering the alarmins and microbial ligands. Although the NLRP3 inflammasome is essential for host defense during infections, the uncontrolled activation and overproduction of IL-1β and IL-18 increases the risk of developing autoimmune and metabolic disorders. The long non-coding RNAs (lncRNAs) is an emerging field of study and evidence on their regulatory role in various diseases is grabbing attention. Recent studies emphasize the functions of lncRNAs in the fine control of the NLRP3 inflammasome at nuclear and cytoplasmic levels by interfering in chromatin architecture, gene transcription and translation. The present review is a novel attempt to consolidate the substantial role of lncRNAs in the regulation of the NLRP3 inflammasome. A deeper insight into the NLRP3 inflammasome regulation by lncRNAs will help in developing targeted and beneficial therapeutics in the future.